Mga pusang gala stray cats - Ongkeko-Marfil, Ellen; Lana, Jun; Vera, Tody (Videoflick Productions, 2006)
A middle-aged advertising practitioner and her aging gay landlord live their lives waiting for men to fulfill their dreams.